INDONESIA LANGUAGE INFLUNCES SHIFTHING IN SIMALUNGUN LANGUAGE - Marhaeni Matondang; Indra Jayanti Damanik (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2020)
This study focused in Indonesia Language influences shifting in Simalungun Language. The problem of the study is “How is Simalungun Language shift in Pematangsiantar.” The objective of the study is to determine the factor influences Simalumgun Language shift in Pematangsiantar. The significance of the research are: 1) Theoritically, the study considered to enrich the theory of language planning especially about Simalungun language shift in Pematangsiantar and the reason of Simalungunese shift into Indonesian. 2) Practically, the result of the study is considered to contribute information about language shift in Simalungunese for the researcher. The findings of the research are Language shift (especially Simalungunism) in the second and the third generation is influence by bilingualism, migration, economic factor, value and attitude, The pattern of Language shift is done through the shift of Simalungun Language to Indonesian Language in second and the third generation and The reason of the language shift (Simalungun language) into Indonesian are social success and the status of Indonesian Language.